Mexican Americans and the Catholic Church, 1900-1965 - Dolan, Jay P.; Hinojosa, Gilberto (Notre Dame, IN : University of Notre Dame Press, 1994)
Within the American Catholic Church the Mexican American legacy is the longest, as is their struggle for full acceptance in the institutional church. In this volume three historians examine religious history, focusing on Mexican American faith communities. Originally published in 1994.
4. A New Era: World War II and After -- 5. Migrants and Braceros -- 6. The Mexican-American Catholic Community Comes of Age, 1960-1965 -- PART III: The Catholic Church and the Making of Mexican-American Parish Communities in the Midwest -- 1. Midwestern Catholicism and the Early Mexican Parishes, 1910-1930 -- 2. Depression, Survival, and Fragmented Religiosity, 1930-1945 -- 3. Parish Growth and Barrio Diversity, 1945-1965 -- NOTES -- CONTRIBUTORS -- Index
Description based upon print version of record.
JSTOR
Keywords: Catholic Church -- United States -- History -- 20th century; Église catholique -- Histoire -- 20e siècle.; Mexican American Catholics -- History; Catholiques américains d'origine mexicaine -- Histoire; RELIGION / Christianity / Catholic; Electronic books